2020
DOI: 10.1001/jamacardio.2020.0109
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Duration of Ideal Cardiovascular Health Through Adulthood With Cardiometabolic Outcomes and Mortality in the Framingham Offspring Study

Abstract: ideal cardiovascular health (CVH) score is associated with the risk of cardiovascular disease (CVD) and mortality. However, it is unclear whether the number of years spent in ideal CVH is associated with morbidity or with mortality.OBJECTIVE To evaluate whether living longer with a higher CVH score in midlife is associated with lower risk of hypertension, diabetes, chronic kidney disease, CVD and its subtypes (coronary heart disease, stroke, congestive heart failure, and peripheral artery disease), or all-caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 36 publications
3
74
0
1
Order By: Relevance
“…The impact of this polymorphism on BP throughout adulthood and the potential modifying effect of riboflavin are important findings, considering that this polymorphism is linked with an increased risk of stroke [ 12 14 ], and recent evidence shows that living longer in better cardiovascular health during mid-life is associated with lower risk of disease and mortality later in life [ 27 ]. Control of BP is highly effective in reducing cardiovascular mortality [ 5 , 23 , 24 ], with each 2 mmHg lower systolic BP associated with a 10% lower risk of stroke [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of this polymorphism on BP throughout adulthood and the potential modifying effect of riboflavin are important findings, considering that this polymorphism is linked with an increased risk of stroke [ 12 14 ], and recent evidence shows that living longer in better cardiovascular health during mid-life is associated with lower risk of disease and mortality later in life [ 27 ]. Control of BP is highly effective in reducing cardiovascular mortality [ 5 , 23 , 24 ], with each 2 mmHg lower systolic BP associated with a 10% lower risk of stroke [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been a lot of research reports that adherence to healthy lifestyle may substantially lower the burden of cardiovascular diseases [49][50][51][52] . Maintaining ICH from early adulthood results in higher health-related quality of life in middle age 10,53 . Even for patients with diabetes and hypertension, maintaining ICH is bene cial to reduce the risk of cardiovascular disease 51,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated the inverse association between the number of ICH metrics and the risks of hypertension 9,10 , type 2 diabetes mellitus 11,12 , CVDevents (stroke, heart failure, myocardial infarction, and fatal coronary disease) [13][14][15][16][17][18][19][20] , CVD mortality 21,22 , all-cause mortality 10,23 and concer 24,25 . However, most of the previous studies were conducted in western countries and Chinese urban areas [26][27][28] , much fewer in Chinese rural areas, which may not completely re ect the characteristics of Chinese rural population.…”
Section: Introductionmentioning
confidence: 99%
“…The EQ-5D utility scores were calculated based on the recently available Chinese value set for the EQ-5D-5L instrument [19]. 3,4,5). Scores ranged from −0.200 to 1.000, with one representing full health, 0 representing death, and a score <0 representing a health status worse than death.…”
Section: Eq-5d-5lmentioning
confidence: 99%